2020
DOI: 10.1038/s41467-020-17740-1
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell analysis uncovers fibroblast heterogeneity and criteria for fibroblast and mural cell identification and discrimination

Abstract: Many important cell types in adult vertebrates have a mesenchymal origin, including fibroblasts and vascular mural cells. Although their biological importance is undisputed, the level of mesenchymal cell heterogeneity within and between organs, while appreciated, has not been analyzed in detail. Here, we compare single-cell transcriptional profiles of fibroblasts and vascular mural cells across four murine muscular organs: heart, skeletal muscle, intestine and bladder. We reveal gene expression signatures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
406
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(432 citation statements)
references
References 75 publications
26
406
0
Order By: Relevance
“…Force-directed layouts following Harmony implementation ordered cells broadly according to their developmental age (days after conception) ( Figure 1D). The day 47 cells were largely separate from other time points, with the exception of an ACTA2 HI / TAGLN HI /RGS5 + population of vascular smooth muscle cells (VSMCs) (Muhl et al, 2020;Figures 1D and 1E). Cells were then ordered according to developmental time, with cells from samples older than 101 days (101, 122, 127, and 132 days) clustering together.…”
Section: Interrogating the Developing Human Small Intestine At Singlementioning
confidence: 99%
“…Force-directed layouts following Harmony implementation ordered cells broadly according to their developmental age (days after conception) ( Figure 1D). The day 47 cells were largely separate from other time points, with the exception of an ACTA2 HI / TAGLN HI /RGS5 + population of vascular smooth muscle cells (VSMCs) (Muhl et al, 2020;Figures 1D and 1E). Cells were then ordered according to developmental time, with cells from samples older than 101 days (101, 122, 127, and 132 days) clustering together.…”
Section: Interrogating the Developing Human Small Intestine At Singlementioning
confidence: 99%
“…However, examining single cell sequencing data for mouse brain pericytes revealed that some also expressed myh11 , while no alpha smooth muscle actin/acta2 expression was detected in this cell population (Vanlandewijck et al, 2018). In line with this assessment, single cell sequencing of mural cell populations of different mouse organs has revealed a surprising diversification of pericytes, also in respect to the expression of components of the SMC contractile machinery, such as myh11, tagln and acta2 (Muhl et al, 2020; Vanlandewijck et al, 2018). In organs such as the bladder or colon, pericytes expressed tagln and acta2 , while in the brain and lung they did not.…”
Section: Discussionmentioning
confidence: 76%
“…Overall, the ontogeny of pericytes and vSMCs is very distinct from that of other specialized SMC types and recent genomewide quantitative transcriptomes studies have highlighted the complexity of this mural cell population in adult organs (Muhl et al, 2020;Vanlandewijck et al, 2018). Interestingly, single-cell transcriptomic analyses of the adult mouse brain have led to the identification of a population of perivascular fibroblast-like cells that are present on all vessel types, except capillaries (Vanlandewijck et al, 2018).…”
Section: Pericytesmentioning
confidence: 99%